REALITA KEHIDUPAN SOSIAL DALAM KUMPULAN CERPEN 'LAGU CINTA UNTUK TUHAN' KARYA ARIS KURNIAWAN: kehidupan sosial - Rochmawati, Dyah (LPPM Universitas PGRI Adi Buana Surabaya, 2014)
Social life is one thing that is described in a work of literature by a novelist. It depicts economic, political, religious, environmental and cultural elements of the novel's world. The author chooses this world specifically to address themes and ideas. Analyzing and undemanding it is crucial for understanding themes, characters and plot. Social life is also represented in Aris Kurniawan's collection of short stories entitled 'Lagu Cinta untuk Tuhan' which means 'A Love Song for God'. This article thus aims at describing how the characters live and dream in the collection of stories- how they follow, question, protest or break the rules of that world. It examines the social issue from acontemporary perspective, assessing its significance in society today. The results showed that the collection revealed the realistic portrayal of a variety of today's social life, inparticular the cruel social wrongs.